An unusual pseudomelanosis in toddlers. - Berti, I.; Bonamonte, D.; Cutrone, M.; Favale, M.G.; Mazzotta, F.; Milano, A.; Rigano, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
An unusual brownish pigmentation of the pelvis and lower limbs in infants which can be easily removed with a towel, to reappear after a few hours was described. The arcane clarifies when a manufacturer of baby cleaning wipes withdrew a lot from the market, holding it responsible for the phenomenon.